Densitas Pohon Dewasa Dan Permudaan Pulai (Alstonia Scholaris) Dan Suren (Toona Sureni) Dalam Blok Koleksi Tumbuhan Di Taman Hutan Raya Wan Abdul Rachman - Andi A. J. Siahaan; Indriyanto Indriyanto; Agus Setiawan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
The plant collection block is a part of the Great Forest Park of Wan Abdul Rachman that contains varie of plant species, either pristine plant or not and rare or not rare which are needed to be protected and preserved. The plant collection block condition has been changed to be cultivation land. This condition is feared can interfere the existence of rare plants species such as devil tree (Alstonia scholaris) and cedar (Toona sureni). This research was done at the plant collection block in Great Forest Park of Wan Abdul Rachman on September - October 2013. This research is aimed to determine the density, distribution, condition, and coordinates position of devil tree and cedar. The data was taken by used checkered lines method with 0.1% sampling intensity. The sampling area was about 8,455.4 m2, then divided into 20 plots. The distance between lines was 200 m and plots was 100 m. The result showed that the devil tree density was higher amount of 15 stems/ha than cedar density of 7 stems/ha in a row. The frequency of devil tree was found in observation plots about 0.25 stems/ha that was higher than cedar frequency which only of 0.15 stems/ha. Cedar grown by 5 stems, that amount the criteria of main tree as many as 1 stem in the 20th plot. Devil tree grown by 4 stems, that amount the criteria of main tree as many as 1 stem in the 19th plot. Keywords: plant collection block, parent tree, rare tree